Human Infections by Wohlfahrtiimonas chitiniclastica: A Mini-Review and the First Report of a Burn Wound Infection after Accidental Myiasis in Central Europe - Hladík, Martin; Lipovy, Bretislav; Kaloudova, Yvona; Hanslianova, Marketa; Vítková, Ivana; Deissova, Tereza; Kempny, Tomas; Svoboda, Martin; Kala, Zdenek; Brychta, Pavel; Borilova Linhartova, Petra (Microorganisms, 2021)
Wohlfahrtiimonas chitiniclastica are bacteria that cause rare infections, typically associated with the infestation of an open wound with fly larvae. Here, we present a unique case report of the first W. chitiniclastica isolation from a burn wound with accidental myiasis in a 63-year-old homeless man and a literature review focused on human infections caused by these bacteria. So far, 23 cases of infection with W. chitiniclastica have been reported; in 52% of these, larvae were found in the wound area. Most of these cases suffered from chronic non-healing wound infections but none of these were burn injuries. The overall fatality rate associated directly with W. chitiniclastica in these cases was 17%. Infections with parasitic larvae occur in moderate climates (especially in people living in poor conditions); therefore, an infection with rare bacteria associated with accidental myiasis, such as W. chitiniclastica, can be expected to become more common there. Thus, in view of the absence of recommendations regarding the treatment of patients with accidental myiasis and, therefore, the risk of infection with W. chitiniclastica or other rare pathogens, we provide a list of recommendations for the treatment of such patients. The importance of meticulous microbial surveillance using molecular biological methods to facilitate the detection of rare pathogens is emphasized.